2019
DOI: 10.3390/rs11040436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Satellite and UAV-Based Multispectral Imagery for Vineyard Variability Assessment

Abstract: In agriculture, remotely sensed data play a crucial role in providing valuable information on crop and soil status to perform effective management. Several spectral indices have proven to be valuable tools in describing crop spatial and temporal variability. In this paper, a detailed analysis and comparison of vineyard multispectral imagery, provided by decametric resolution satellite and low altitude Unmanned Aerial Vehicle (UAV) platforms, is presented. The effectiveness of Sentinel-2 imagery and of high-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
139
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 49 publications
(55 reference statements)
11
139
0
4
Order By: Relevance
“…For a smaller observation area, such as a farm block, an irrigation zone, a single row of the horticultural crop, or a single canopy, this spatial resolution is considered sub-optimal. Often, a pixel of the satellite image comprises of multiple rows and multiple canopies of horticultural crops [42,56]. Thus, the spectral response on a single pixel of the satellite image includes a mixed spectral signal from the canopy, inter-row vegetation and/or bare soil.…”
Section: Satellite Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a smaller observation area, such as a farm block, an irrigation zone, a single row of the horticultural crop, or a single canopy, this spatial resolution is considered sub-optimal. Often, a pixel of the satellite image comprises of multiple rows and multiple canopies of horticultural crops [42,56]. Thus, the spectral response on a single pixel of the satellite image includes a mixed spectral signal from the canopy, inter-row vegetation and/or bare soil.…”
Section: Satellite Systemsmentioning
confidence: 99%
“…Thus, the spectral response on a single pixel of the satellite image includes a mixed spectral signal from the canopy, inter-row vegetation and/or bare soil. The mixed-pixel is particularly unavoidable in horticultural crops with large inter-row surfaces, introducing errors in satellite-based estimations [42,56]. Improving the spatial resolution from freely available Landsat/Sentinel satellites (spatial resolution 10-15 m) to such as WorldView-3 (spatial resolution 0.3 m), does not necessarily resolve single canopies of many horticultural crops.…”
Section: Satellite Systemsmentioning
confidence: 99%
“…There have been some related works done in this area. Khaliq et al [51] compared satellite imagery with UAV-based multispectral data in four different epochs of the grapevines' vegetative cycle. Different comparisons were made by considering: (i) the whole vineyard, (ii) only the grapevines' vegetation, and (iii) only inter-row areas.…”
Section: Introductionmentioning
confidence: 99%
“…With reference to multi-temporal studies, there are those whose aim is to compare different growing seasons by evaluating biophysical grapevines parameters [54][55][56]. Furthermore, studies utilizing intra-season multi-temporal data, considered the whole vineyard information [57] or vineyard changes were not the main focus [51]. As found in Primicerio et al [22], vigour maps using only grapevines' vegetation showed a better representation of the variability within the vineyard.…”
Section: Introductionmentioning
confidence: 99%
“…UAV data creates new opportunities in agriculture [18][19][20], e.g., assessment of plant health status [21], water stress [22], management techniques [23], erosion of soils [24], and detection of individual plants [25], among many others. The advantages of VHR data sets compared to common satellite data sets have also been analyzed, e.g., for vegetation indices (VI) [26,27]. Further, UAVs have the ability to acquire data in a very flexible manner, e.g., by considering changing weather conditions, and they are cheap to operate compared to other carrier systems [17].…”
Section: Introductionmentioning
confidence: 99%